2020
DOI: 10.14198/jhse.2020.152.02
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the shots in positions 1 and 2 in even situational framework during the World Championship of Barcelona 2013

Abstract: The purpose of this study was, on one hand, to know if the left-handed players were more effective in the goal categories and getting positive actions in 1 and 2 position than the right-handed in the same offense position in Even Situational Framework (FJa). On the other hand, to know if the shots in 1 and 2 position were less effective than the rest of the positions in the goal categories. The methodology was observational, multidimensional, nomothetic and punctual. The sample was all the throws of 24 games (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In particular, technical and tactical studies have been focused on team efficacy (Argudo et al, 2007(Argudo et al, , 2008Lupo et al, 2009), tactical roles (Lupo et al, 2012), a competition level (Lupo et al, 2010), match outcomes (Argudo et al, 2007(Argudo et al, , 2009 and margin of victory (Gomez et al, 2014;Lupo et al, 2012Lupo et al, , 2014. Descriptive studies of the game (Canossa et al, 2009), analysis of technical actions (Alcaraz et al, 2011;Vila et al, 2011), specific playing positions (Sabio et al, 2020) and notational analysis (Argudo et al 2007;Lupo et al, 2014). Also the analysis of the playing action in Water polo has looked for technical and tactical performance indicators (Escalante et al, 2012;Mirvic et al, 2011), characterized the type of actions and their physical demands in relation to their intensity (D´Auria & Gabbet, 2008;Lupo et al, 2009), described the game profiles for each specific position (Lozovina et al, 2010;Lupo et al, 2012), found the effects of the regulatory changes (Argudo et al, 2020), analysed the influence of time out (Platanou, 2008), game location (Prieto et al, 2013), scoreboard result (Lupo et al, 2012), for having the first ball possession of each period (Argudo, 2010); and, calculated the effectiveness in each situational framework (Argudo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, technical and tactical studies have been focused on team efficacy (Argudo et al, 2007(Argudo et al, , 2008Lupo et al, 2009), tactical roles (Lupo et al, 2012), a competition level (Lupo et al, 2010), match outcomes (Argudo et al, 2007(Argudo et al, , 2009 and margin of victory (Gomez et al, 2014;Lupo et al, 2012Lupo et al, , 2014. Descriptive studies of the game (Canossa et al, 2009), analysis of technical actions (Alcaraz et al, 2011;Vila et al, 2011), specific playing positions (Sabio et al, 2020) and notational analysis (Argudo et al 2007;Lupo et al, 2014). Also the analysis of the playing action in Water polo has looked for technical and tactical performance indicators (Escalante et al, 2012;Mirvic et al, 2011), characterized the type of actions and their physical demands in relation to their intensity (D´Auria & Gabbet, 2008;Lupo et al, 2009), described the game profiles for each specific position (Lozovina et al, 2010;Lupo et al, 2012), found the effects of the regulatory changes (Argudo et al, 2020), analysed the influence of time out (Platanou, 2008), game location (Prieto et al, 2013), scoreboard result (Lupo et al, 2012), for having the first ball possession of each period (Argudo, 2010); and, calculated the effectiveness in each situational framework (Argudo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%